Ethics and Humanization in Artificial Intelligence-Based History Learning - Silvy Mei Pradita; Didin Saripudin; Leli Yulifar; Erlina Wiyanarti (JTP - Jurnal Teknologi Pendidikan, 2025)
The development of Artificial Intelligence (AI) has brought significant changes to the field of education, including history learning. This article aims to analyze in depth the philosophical, ethical, and practical implications of utilizing AI in history learning, particularly in the context of character development and students’ academic integrity. This study employs a literature review with a descriptive-analytical approach, examining various scholarly sources on the use of AI technology in education. This includes educators at various levels, AI technology developers, education policymakers, students as primary users, and the wider community with a stake in the education system. The initial goal of artificial intelligence was to make human work easier, but over time, artificial intelligence has become a dilemma, trapping humans in a spiral of pseudo-intelligence. This has undoubtedly changed many models of human interaction. Based on this, a more humane digital life is needed.A life that is enlightening by prioritizing human intelligence (analog) rather than artificial intelligence (digital), which shackles humans in the context of the digital shadow that enslaves humanism.This ensures that the humanistic touch of art is not easily disrupted by artificial intelligence. This research adopts a qualitative approach to in-depth explore various aspects of AI use in education. The primary objective of this research is to identify and analyze the potential benefits of integrating artificial intelligence into education.